Design and development of a digital library of bibliographic data of theses and dissertations. - Foo, Toon Seng. (2008)
The main objective of this project was to develop a digital library of bibliographic data of theses and dissertations for the Asian Communication Resource Centre (ACRC). This project was specifically motivated to meet the needs of lecturers and students in the School of Communication and Information (SCI) of Nanyang Technological University (NTU) in using the proposed digital library to browse and search for theses and dissertations.